2015
DOI: 10.1016/j.eururo.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Combined Value of Validated Clinical and Genomic Risk Stratification Tools for Predicting Prostate Cancer Mortality in a High-risk Prostatectomy Cohort

Abstract: Background Risk prediction models that incorporate biomarkers and clinicopathologic variables may be used to improve decision-making post radical prostatectomy (RP). We compared two previously validated post-RP classifiers—the Cancer of the Prostate Risk Assessment post-Surgical (CAPRA-S) and the Decipher genomic classifier (GC)—to predict prostate cancer-specific mortality (CSM) in a contemporary cohort of RP patients. Objective To evaluate the combined prognostic ability of CAPRA-S and GC to predict CSM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 25 publications
6
138
1
Order By: Relevance
“…This panel has also been externally validated in multiple cohorts and is commercially available as the Decipher genetic test (GenomeDX Biosciences, Vancouver, BC, Canada). Four studies reported the utilization of this gene panel to predict BCR, metastatic progression, or DSS after RP plus or minus EBRT [61,[71][72][73]. The prognostic accuracy was highest when the genomic classifier and clinical models (CAPRA-S) were combined [61].…”
Section: External Validation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This panel has also been externally validated in multiple cohorts and is commercially available as the Decipher genetic test (GenomeDX Biosciences, Vancouver, BC, Canada). Four studies reported the utilization of this gene panel to predict BCR, metastatic progression, or DSS after RP plus or minus EBRT [61,[71][72][73]. The prognostic accuracy was highest when the genomic classifier and clinical models (CAPRA-S) were combined [61].…”
Section: External Validation Studiesmentioning
confidence: 99%
“…The biomarkers to be included in clinical decision making have to provide additional independent prognostic information or additive value together with established clinical and pathologic variables in a multivariate setting like the Memorial Sloan Kettering Cancer Center or Cleveland Clinic nomograms or Cancer of the Prostate Risk Assessment Postsurgical (CAPRA-S) risk stratification for PCa. [54,60,61]. A few studies investigated TURP tissue to predict the outcome of men undergoing conservative treatment [51,62,63].…”
Section: Gene/expression Panelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refinement of the high-density micro-arrays from roughly 1.4 million features was performed using machine learning algorithms to select a panel of markers highly associated with clinical outcomes. The Decipher score (reported on a 0-1 scale) predicting early metastatic progression following RP was examined in a cohort of men with adverse pathological features, where increases in the GC score were significantly associated with metastatic progression and PCSM, even after adjustment for the CAPRA-S score or other models incorporating postprostatectomy data [42,43] The Decipher genomic classifier was evaluated for the ability to selectively identify men who may benefit from adjuvant radiation therapy following RP [44]. Den et al reported on 188 men with pathological T3 or marginpositive PCa at surgery who were treated with adjuvant radiation therapy at two institutions between 1990 and 2009.…”
Section: Decipher (Genomedx Vancouver Bc)mentioning
confidence: 99%
“…Recently, various genomic predictors have allowed for refinement of prognosis across all risk strata of localized prostate cancer (5,6). These tools harness tumor characteristics to define recurrence risk -ostensibly, features of the tumor microenvironment may also predict clinical outcome.…”
Section: Introductionmentioning
confidence: 99%